Acidosis, but not alkalosis, affects anaerobic metabolism and performance in a 4-km time trial - Correia-Oliveira, C. R.; Lopes-Silva, J. P.; Bertuzzi, R.; McConell, G. K.; Bishop, D. J.; Lima-Silva, A. E.; Kiss, M. A. P. D. (Medicine & Science in Sports & Exercise, 2017)
Purpose: This study aimed to determine the effect of preexercise metabolic acidosis and alkalosis on power output (PO) and aerobic and anaerobic energy expenditure during a 4-km cycling time trial (TT).